Influenza vaccine effectiveness against hospitalisation with influenza in adults in Australia in 2014. Issue 51 (16th December 2015) - Cheng, Allen C.; Kotsimbos, Tom; Kelly, Paul M.; ,
Highlights: Between April and November 2014, 1692 adult patients were admitted with influenza to a sentinel hospital network in Australia. Vaccine effectiveness was estimated from 1283 patients with influenza and 1116 test negative patients where vaccination status was ascertained. Vaccination was associated with a reduction in the risk of hospitalisation with influenza of 51.5% (41.6%, 59.7%, p  < 0.001). Abstract: We provide estimates of the influenza vaccine protection against hospitalisation with laboratory-confirmed influenza in the 2014 Australian season where the A/H1N1/pdm09 strain predominated. This was performed using a case-test negative study design as part of a national sentinel surveillance system in Australia. Vaccine effectiveness was estimated as (1-OR) × 100% where the odds ratio of vaccination in cases vs test negative participants was estimated from a conditional logistic regression. Between April and November, 1692 adult patients were admitted with laboratory-confirmed influenza. Vaccine effectiveness was estimated from 1283 patients with influenza and 1116 test negative patients where vaccination status was ascertained. Vaccination was associated with a reduction in the risk of hospitalisation with influenza of 51.5% (95% CI: 41.6%, 59.7%) in all patients, and a reduction of 50.7% (95% CI: 40.1%, 59.3%) in the target population for vaccination. We estimate that the influenza vaccine was moderately protective against hospitalisation with laboratory-confirmed influenza during the 2014 influenza season in Australia.